Discussion: a critique of Possible waterways between the Marmara Sea and the Black Sea in the late Quaternary: evidence from ostracod and foraminifer assemblages in lakes İznik and Sapanca, Turkey, Geo-Marine Letters, 2011 - Yaltırak, Cenk; Ülgen, Umut B.; Zabcı, Cengiz; Franz, Sven Oliver; Ön, Sena Akçer; Sakınç, Mehmet; Çağatay, M. Namık; Alpar, Bedri; Öztürk, Kurultay; Tunoğlu, Cemal; Ünlü, Selma; Zabcı, Cengiz (Springer Science and Business Media LLC, 2011)
The identification of past connection routes between the Black Sea and the Sea of Marmara, other than the traditional one through to the Bosphorus Strait, would be of considerable interest to the international scientific community. Nazik et al. (Geo-Mar Lett 31:75–86 (2011) doi: 10.1007/s00367-010-0216-9 ) suggest the possibility of two alternative waterway connections via lakes Sapanca and Iznik. Their Black Sea to Sea of Marmara multi-connection hypothesis, which is based on undated marine fossils collected in both lakes from surficial grab samples, conflicts with many earlier studies. In this contribution, the hypothesis and the underlying data are discussed in the light of previous tectonic, sedimentological and limnological findings showing that it is impossible to have had marine connections through lakes Sapanca and Iznik during the last 11.5 ka. Global sea-level trends and tectonic uplift rates would accommodate a connection between the Sea of Marmara and Lake Iznik in the middle Pleistocene. Uplift rates for the northern block of the North Anatolian Fault, when compared with the global sea-level curve, clearly indicate that there cannot have been a connection through the Izmit Gulf–Lake Sapanca–Sakarya Valley for at least the past 500 ka. Moreover, borehole sediments along the western shores of Lake Sapanca, which reach down to the bedrock, do not contain any marine fossils.